Economic variables affecting services in private schools - Abbas, Hala; Khudhaur , Liqaa (Al-Adab Journal, 2025)
The research seeks to reveal the reality of private schools and learn about the quality of learning services provided by private schools, and spatial distribution in accordance with Iraqi standards for private schools, and aims to study economic changes affecting educational services in private schools. To achieve this, the descriptive and analytical approach and the quantitative style were used, and the data was classified in statistical tables and turned into rates and percentages to compare them at the level of neighborhoods, as well as the use of maps and graphs, and the standard degree was adopted as a measure to clarify the variation of economic variables in the subject of research. To reach the spatial relations related to private schools, the statistical bag (SPSS) adopted the Person correlation laboratories, and the research in its data relied on the official publications of the Central Agency for Statistics and Technology Information, and the data of the Ministry of Education, the first Rusafa Education Directorate and the third Karkh Education Directorate, and the field study for the year 2023. The research reached a set of results, the most important of which is the satisfaction of the researchers on private education, as the number of private schools in Al -Adhamiya municipality reached (52) schools distributed in the neighborhoods, and the highest number of private schools reached (14) schools in Al -Shammasia neighborhood, and the number of private schools in Al -Kadhimiya municipality reached ( 33) School, which numbered (13) schools in the Al -Zahra and Al -Athifiya neighborhood, that the researchers see that private schools are investment projects aimed at money and not a better education, and that most schools were established without regard to the criteria set by the state.